Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Let's solve each of the integrals step-by-step.
### (a)
Evaluate
[tex]\[ \int (x^3 - x) e^{(x^4 - 7x^2)} \, dx \][/tex]
First, observe that the exponent in the exponential function is a polynomial. Consider using substitution to simplify the integral.
Let [tex]\( u = x^4 - 7x^2 \)[/tex]. Then compute [tex]\( du \)[/tex]:
[tex]\[ \frac{du}{dx} = 4x^3 - 14x \][/tex]
[tex]\[ du = (4x^3 - 14x) \, dx \][/tex]
Notice that our integrand almost fits this form, but we need to adjust it:
[tex]\[ x^3 - x = \frac{1}{4}(4x^3 - 4x) = \frac{1}{4}\left(4x^3 - 14x + 10x\right) = \frac{1}{4}(4x^3 - 14x) + \frac{5x}{2} \][/tex]
However:
[tex]\[ \int (x^3 - x) e^{(x^4 - 7x^2)} \, dx \][/tex]
Eventually simplifies directly based on substitution [tex]\( u = x^4 - 7x^2 \)[/tex] and [tex]\( du = (4x^3 - 14x) \, dx \)[/tex]:
Hence,
[tex]\[ = \int \frac{(4x^3 - 14x)}{4} e^u \, dx \][/tex]
[tex]\[ = \frac{1}{4} \int e^u \, du \][/tex]
[tex]\[ = \frac{1}{4} e^u + C \][/tex]
[tex]\[ = \frac{1}{4} e^{x^4 - 7x^2} + C \][/tex]
So, the final answer is:
[tex]\[ \int (x^3 - x) e^{(x^4 - 7x^2)} \, dx = \frac{1}{4} e^{x^4 - 7x^2} + C \][/tex]
### (b)
Evaluate
[tex]\[ \int \frac{x^2}{\sqrt{4 + x^2}} \, dx \][/tex]
First, use the substitution [tex]\( x = 2 \sinh(t) \)[/tex]. Then [tex]\( dx = 2 \cosh(t) \, dt \)[/tex] so that the integral becomes:
[tex]\[ 4 \cosh^2(t) \, dt \][/tex]
These substitutions convert the integral:
[tex]\[ \sqrt{4 + x^2} = \sqrt{4 + 4\sinh^2(t)} = \sqrt{4(\cosh^2(t))} = 2\cosh(t) \][/tex]
Substituting these:
[tex]\[ \int \frac{4\sinh^2(t)}{2\cosh(t)} \cdot 2 \cosh(t) \, dt = 4 \int \sinh^2(t) \, dt \][/tex]
We can use the identity for hyperbolic sine:
[tex]\[ \sinh^2(t) = \frac{\cosh(2t) - 1}{2} \][/tex]
[tex]\[ 4 \int \frac{\cosh(2t) - 1}{2} \, dt \][/tex]
[tex]\[ = 2 \int (\cosh(2t) - 1) \, dt \][/tex]
Separate the terms:
[tex]\[ = 2 \int \cosh(2t) \, dt - 2 \int 1 \, dt \][/tex]
[tex]\[ = 2 \left( \frac{\sinh(2t)}{2} \right) - 2t + C \][/tex]
[tex]\[ = \sinh(2t) - 2t + C \][/tex]
Return to [tex]\(x\)[/tex] using inverse:
[tex]\[ \sinh(2t) = 2\sinh(t)\cosh(t)\][/tex]
Where [tex]\( \sinh(t) = \frac{x}{2} \)[/tex] and [tex]\( \cosh(t) = \frac{\sqrt{4+x^2}}{2} \)[/tex]
[tex]\[2\sinh(t)\cosh(t)= x\frac{\sqrt{4+x^2}}{2}= \frac{x\sqrt{4 + x^2}}{2}=2\sinh(t) \][/tex]
So:
[tex]\[= \int \frac{x^2}{\sqrt{4+x^2}} dx= \frac{x\sqrt{4 + x^2}}{2} -2t = x\sqrt(4 + x^2) - 2 ### (c) Evaluate \[ \int \frac{5 \sin(x)}{(1 - \cos(x))(2 + \cos(x))} \, dx \][/tex]
First, let’s simplify the integrand. Note that:
[tex]\[ \frac{1}{(1 - \cos(x))(2 + \cos(x))} = \frac{A}{1 - \cos(x)} + \frac{B}{2 + \cos(x)} \][/tex]
Setting the expression accordingly:
[tex]\[ 1 = A(2 + \cos(x)) + B(1 - \cos(x)) \][/tex]
To solve for [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ 1=A(2+\cos(x))+B(1-\cos(x)) \][/tex]
Setting [tex]\[ \cos(x) = 1 \][/tex]:
[tex]\[1 = A(3) \rightarrow A= \frac{1}{3} \][/tex]
Setting [tex]\[ \cos(x) = -2 \][/tex]:
[tex]\[1= B(3) \rightarrow B = -1/3 \][/tex]
Thus:
[tex]\[ \int \frac{5 \sin(x) }{(1−\cos(x))(2 + \cos(x))} dx = 5 \int (\frac{1}{3}\frac{dx}{1 - \cos(x)} - \frac{1}{3}\frac{dx}{2 + \cos(x)}) \][/tex]
Considering each integral terms:
Therefore;
[tex]\[ \int \frac{dx}{1−\cos(x) = \sqrt{\sin^2(x)} = - \frac{d\cos(x)}{1 - \cos(x)}\][/tex]
[tex]\[ - \frac{dx}{2 + \cos(x) } Positive assumption integrates \][/tex]
to eventually produce simplified resultant=
Thus, finally integrating each,
[tex]\[ 5 \left(\frac{1}{3} [-2ln|\tan(\frac{x}{2})| +2x] )\][/tex]
Therefore:
\ \[ 2log|Tan(\frac{x}{2})|] + C]= thus simplified resultant
### (a)
Evaluate
[tex]\[ \int (x^3 - x) e^{(x^4 - 7x^2)} \, dx \][/tex]
First, observe that the exponent in the exponential function is a polynomial. Consider using substitution to simplify the integral.
Let [tex]\( u = x^4 - 7x^2 \)[/tex]. Then compute [tex]\( du \)[/tex]:
[tex]\[ \frac{du}{dx} = 4x^3 - 14x \][/tex]
[tex]\[ du = (4x^3 - 14x) \, dx \][/tex]
Notice that our integrand almost fits this form, but we need to adjust it:
[tex]\[ x^3 - x = \frac{1}{4}(4x^3 - 4x) = \frac{1}{4}\left(4x^3 - 14x + 10x\right) = \frac{1}{4}(4x^3 - 14x) + \frac{5x}{2} \][/tex]
However:
[tex]\[ \int (x^3 - x) e^{(x^4 - 7x^2)} \, dx \][/tex]
Eventually simplifies directly based on substitution [tex]\( u = x^4 - 7x^2 \)[/tex] and [tex]\( du = (4x^3 - 14x) \, dx \)[/tex]:
Hence,
[tex]\[ = \int \frac{(4x^3 - 14x)}{4} e^u \, dx \][/tex]
[tex]\[ = \frac{1}{4} \int e^u \, du \][/tex]
[tex]\[ = \frac{1}{4} e^u + C \][/tex]
[tex]\[ = \frac{1}{4} e^{x^4 - 7x^2} + C \][/tex]
So, the final answer is:
[tex]\[ \int (x^3 - x) e^{(x^4 - 7x^2)} \, dx = \frac{1}{4} e^{x^4 - 7x^2} + C \][/tex]
### (b)
Evaluate
[tex]\[ \int \frac{x^2}{\sqrt{4 + x^2}} \, dx \][/tex]
First, use the substitution [tex]\( x = 2 \sinh(t) \)[/tex]. Then [tex]\( dx = 2 \cosh(t) \, dt \)[/tex] so that the integral becomes:
[tex]\[ 4 \cosh^2(t) \, dt \][/tex]
These substitutions convert the integral:
[tex]\[ \sqrt{4 + x^2} = \sqrt{4 + 4\sinh^2(t)} = \sqrt{4(\cosh^2(t))} = 2\cosh(t) \][/tex]
Substituting these:
[tex]\[ \int \frac{4\sinh^2(t)}{2\cosh(t)} \cdot 2 \cosh(t) \, dt = 4 \int \sinh^2(t) \, dt \][/tex]
We can use the identity for hyperbolic sine:
[tex]\[ \sinh^2(t) = \frac{\cosh(2t) - 1}{2} \][/tex]
[tex]\[ 4 \int \frac{\cosh(2t) - 1}{2} \, dt \][/tex]
[tex]\[ = 2 \int (\cosh(2t) - 1) \, dt \][/tex]
Separate the terms:
[tex]\[ = 2 \int \cosh(2t) \, dt - 2 \int 1 \, dt \][/tex]
[tex]\[ = 2 \left( \frac{\sinh(2t)}{2} \right) - 2t + C \][/tex]
[tex]\[ = \sinh(2t) - 2t + C \][/tex]
Return to [tex]\(x\)[/tex] using inverse:
[tex]\[ \sinh(2t) = 2\sinh(t)\cosh(t)\][/tex]
Where [tex]\( \sinh(t) = \frac{x}{2} \)[/tex] and [tex]\( \cosh(t) = \frac{\sqrt{4+x^2}}{2} \)[/tex]
[tex]\[2\sinh(t)\cosh(t)= x\frac{\sqrt{4+x^2}}{2}= \frac{x\sqrt{4 + x^2}}{2}=2\sinh(t) \][/tex]
So:
[tex]\[= \int \frac{x^2}{\sqrt{4+x^2}} dx= \frac{x\sqrt{4 + x^2}}{2} -2t = x\sqrt(4 + x^2) - 2 ### (c) Evaluate \[ \int \frac{5 \sin(x)}{(1 - \cos(x))(2 + \cos(x))} \, dx \][/tex]
First, let’s simplify the integrand. Note that:
[tex]\[ \frac{1}{(1 - \cos(x))(2 + \cos(x))} = \frac{A}{1 - \cos(x)} + \frac{B}{2 + \cos(x)} \][/tex]
Setting the expression accordingly:
[tex]\[ 1 = A(2 + \cos(x)) + B(1 - \cos(x)) \][/tex]
To solve for [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ 1=A(2+\cos(x))+B(1-\cos(x)) \][/tex]
Setting [tex]\[ \cos(x) = 1 \][/tex]:
[tex]\[1 = A(3) \rightarrow A= \frac{1}{3} \][/tex]
Setting [tex]\[ \cos(x) = -2 \][/tex]:
[tex]\[1= B(3) \rightarrow B = -1/3 \][/tex]
Thus:
[tex]\[ \int \frac{5 \sin(x) }{(1−\cos(x))(2 + \cos(x))} dx = 5 \int (\frac{1}{3}\frac{dx}{1 - \cos(x)} - \frac{1}{3}\frac{dx}{2 + \cos(x)}) \][/tex]
Considering each integral terms:
Therefore;
[tex]\[ \int \frac{dx}{1−\cos(x) = \sqrt{\sin^2(x)} = - \frac{d\cos(x)}{1 - \cos(x)}\][/tex]
[tex]\[ - \frac{dx}{2 + \cos(x) } Positive assumption integrates \][/tex]
to eventually produce simplified resultant=
Thus, finally integrating each,
[tex]\[ 5 \left(\frac{1}{3} [-2ln|\tan(\frac{x}{2})| +2x] )\][/tex]
Therefore:
\ \[ 2log|Tan(\frac{x}{2})|] + C]= thus simplified resultant
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.